Effect of volatile solvent and evaporation time on formation and performance of PVC/PVC-g-PEGMA blended membranes. Issue 59 (25th October 2019) - Wu, Qidong; Xie, Wancen; Wu, Haibo; Wang, Liang; Liang, Songmiao; Chang, Haiqing; Liu, Baicang
Abstract : The synthesis process of the PVC/PVC- g -PEGMA membranes. Abstract : In order to further improve the performances of fabricated PVC/PVC- graft -poly(ethylene glycol) methyl ether methacrylate (PVC/PVC- g -PEGMA) blended membranes, we investigated the inner connections between affecting parameters during preparation and membrane performances. Two parameters including the composition of casting solutions and the solvent evaporation time were selected. In this study, PVC/PVC- g -PEGMA blended membranes were prepared by non-solvent induced phase separation (NIPS) using 1-methyl-2-pyrrolidinone (NMP) and tetrahydrofuran (THF) as mixing solvents. We found that (1) the membrane morphologies like surface pore size and porosity decreased as the ratio of THF to NMP increased, which resulted in the decrease in pure water flux and the increase of sodium alginate (SA) rejection ratio; (2) the presence of THF in the casting solution could significantly lower the membrane surface roughness compared to only using NMP as a solvent; (3) solvent evaporation for an appropriate time increased the hydrophilicity of the membrane. Among these findings, we achieved a membrane exhibiting the highest flux recovery ratio of 98.65 ± 0.85% with a mixing ratio of 1 : 9 (THF : NMP) at 60 s of evaporation time. High pollutant rejection and high flux recovery ratio were achieved. This study provides more insight into the PVC/PVC- g -PEGMA membrane and a more flexible approach to the application of PVC membranes.